Synthesizing Number Transformations from Input-Output Examples - Singh, Rishabh; Gulwani, Sumit (24th International Conference on Computer Aided Verification (CAV 2012), 2012)
Numbers are one of the most widely used data type in programming languages. Number transformations like formatting and rounding present a challenge even for experienced programmers as they find it difficult to remember different number format strings supported by different programming languages. These transformations present an even bigger challenge for end-users of spreadsheet systems like Microsoft Excel where providing such custom format strings is beyond their expertise. In our extensive case study of help forums of many programming languages and Excel, we found that both programmers and end-users struggle with these number transformations, but are able to easily express their intent using input-output examples. In this paper, we present a framework that can learn such number transformations from very few input-output examples. We first describe an expressive number transformation language that can model these transformations, and then present an inductive synthesis algorithm that can learn all expressions in this language that are consistent with a given set of examples. We also present a ranking scheme of these expressions that enables efficient learning of the desired transformation from very few examples. By combining our inductive synthesis algorithm for number transformations with an inductive synthesis algorithm for syntactic string transformations, we are able to obtain an inductive synthesis algorithm for manipulating data types that have numbers as a constituent sub-type such as date, unit, and time. We have implemented our algorithms as an Excel add-in and have evaluated it successfully over several benchmarks obtained from the help forums and the Excel product team.